2014
DOI: 10.1158/2159-8290.cd-13-0879
|View full text |Cite
|
Sign up to set email alerts
|

EGFR Variant Heterogeneity in Glioblastoma Resolved through Single-Nucleus Sequencing

Abstract: Glioblastomas with EGFR amplification represent approximately 50% of newly diagnosed cases and recent studies have revealed frequent coexistence of multiple EGFR aberrations within the same tumor with implications for mutation cooperation and treatment resistance. However, bulk tumor sequencing studies cannot resolve the patterns of how the multiple EGFR aberrations coexist with other mutations within single tumor cells. Here we applied a population-based single-cell whole genome sequencing methodology to char… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
208
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 251 publications
(223 citation statements)
references
References 54 publications
3
208
1
1
Order By: Relevance
“…We did not evaluate the prognostic role of less common EGFR deletion variants like EGFRvII (deletion of exon [14][15] and EGFRvV (C-terminal deletions; refs. 8,60,62,63); however, a previous study based on TCGA data did not observe a different outcome in glioblastoma patients whose tumors carried either of these variants (61).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…We did not evaluate the prognostic role of less common EGFR deletion variants like EGFRvII (deletion of exon [14][15] and EGFRvV (C-terminal deletions; refs. 8,60,62,63); however, a previous study based on TCGA data did not observe a different outcome in glioblastoma patients whose tumors carried either of these variants (61).…”
Section: Discussionmentioning
confidence: 65%
“…Several studies have reported on various other EGFR sequence alterations than EGFRvIII in glioblastomas, including SNVs as well as larger rearrangements/deletions affecting the extracellular or intracellular domains (8,14,(57)(58)(59)(60)(61)(62)(63). We therefore additionally investigated 27 pairs of primary and recurrent glioblastomas for other EGFR gene alterations using targeted next-generation sequencing of tumor DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Single cell genome sequencing has revealed extensive variability in the degree of EGFR gene amplification and expression of mutated forms of the EGFR, among different tumor cells in a single GBM (54). Soluble factors released by one cell may affect properties of neighboring cells, including the capacity for migration, invasion, and survival.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, single-cell DNA-seq can be achieved by performing single nuclei sorting from fresh frozen tissue. This approach can have even higher resolution to unravel evolutionary relationships among subclonal populations (22,23).…”
Section: Recent Genomic Studies Of Premalignant Diseasementioning
confidence: 99%